Analisis Perkembangan Fisik Kota Palu Dengan Citra Landsat - Rifai (JURNAL RUANG / ISSN : 2085-6962, 2011)
It is proved that the use of remote sensing imagery as urban analysis tool is reduces enormous time on collecting data and improving the quality of spatial analysis. This study is to use the ability of remote sensing on investigate the urban physic pattern in Palu during the year of 1972, 1990 and 2001. Using maximum likelihood methods, these three image satellite of Palu is classified in to 4 different classes, and develop information from this classified image on what type actually formed during the three year of where the image was taken. Although Kota Palu is shown concentric development pattern, the result of this study is find that during the three phases, this city also shown different variant type of urban development on it fringe area.